High‐Resolution X‐ray Absorption and Emission Spectroscopy for Detailed Analysis of New CO2 Methanation Catalysts - Strübbe, Sven; Nowakowski, Michał; Schoch, Roland; Bauer, Matthias (ChemPhysChem)
Abstract A new approach for the characterization of CO 2 methanation catalysts prepared by thermal decomposition of a nickel MOF by hard X‐ray photon‐in/photon‐out spectroscopy in form of high energy resolution fluorescence detected X‐ray absorption near edge structure spectroscopy (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is presented. In contrast to conventional X‐ray absorption spectroscopy, the increased resolution of both methods allows a more precise phase determination of the final catalyst, which is influenced by the conditions during MOF decomposition.
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Monolayer AsTe2: Stable Robust Metal in 2D, 1D and 0D - Badalov, S. V.; Kandemir, A.; Sahin, H. (ChemPhysChem)

Electroluminescent and Optoelectronic Properties of OLEDs with Bay-Extended, Distorted Perylene Esters as Emitter Materials - Vollbrecht, Joachim; Blazy, Simon; Dierks, Philipp; Peurifoy, Samuel; Bock, Harald; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Effect of Alignment on a Liquid Crystal/Split-Ring Resonator Metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (ChemPhysChem)

Synthesis of Liquid Crystal Silane-Functionalized Gold Nanoparticles and Their Effects on the Optical and Electro-Optic Properties of a Structurally Related Nematic Liquid Crystal - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Nanoparticle Doping in Nematic Liquid Crystals: Distinction between Surface and Bulk Effects by Numerical Simulations - Urbanski, Martin; Mirzaei, Javad; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

A New Iron-Based Carbon Monoxide Oxidation Catalyst: Structure-Activity Correlation - Schoch, Roland; Huang, Heming; Schünemann, Volker; Bauer, Matthias (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Insights into the Induced Ultrafast Electron Delocalization in Fe(CO)5 Using Dark Channel Fluorescence Yield X-Ray Absorption - Bauer, Matthias; Stalinski, Tom; Aziz, Emad F. (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Towards X-Ray Absorption Spectroscopy in Real Time - Bauer, Matthias; Bertagnolli, Helmut (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics